The research progress of biologics in elderly-onset rheumatoid arthritis (EORA) - Li, Yujie; Liu, Yifan; Tian, Yanhui; Gu, Huimin; Meng, Qingliang; Cui, Jiakang; Ma, Junfu (Frontiers in Aging, 2025)
Elderly-onset rheumatoid arthritis (EORA) is a distinct subtype of rheumatoid arthritis characterized by heightened treatment challenges due to immune aging and the complexity of comorbidities. This review systematically summarizes the definition, clinical features, epidemiological trends, therapeutic challenges, and the potential applications of biologic agents in EORA. It primarily focuses on the efficacy, safety, and individualized treatment strategies associated with various biologic agents. Studies indicate that biologics, such as TNF-α inhibitors, IL-6 inhibitors, and JAK inhibitors, can significantly reduce inflammation and improve joint function in EORA patients. However, their long-term use is closely linked to increased risks of infections, thrombosis, and malignancies, underscoring the importance of personalized treatment approaches and dynamic monitoring. Moreover, the advent of novel biologic agents, including IL-17 and IL-23 inhibitors, as well as second-generation JAK inhibitors, offers additional therapeutic options for refractory patients and demonstrates substantial potential in optimizing both efficacy and safety. With the rapid progress of precision medicine and artificial intelligence (AI) technologies, gene profiling, biomarker analysis, and AI-assisted decision-making are gradually steering EORA treatment towards more personalized and precise strategies. However, the high cost of treatment and the limited accessibility of these technologies remain significant barriers in clinical practice. Future research should focus on validating the long-term safety of novel therapies and refining individualized treatment strategies to enhance patient outcomes and quality of life.